Bioaccumulation of metal cations by yeast and yeast cell components - Brady, Dean (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1993)
The aim of the project was to determine whether a by-product of industrial fermentations, Saccharomyces cerevisiae, could be utilized to bioaccumulate heavy metal cations and to partially define the mechanism of accumulation. S. cerevisiae cells were found to be capable of accumulating CuÂ²â ºin a manner that was proportional to the external CuÂ²â º concentration and inversely proportional to the concentration of biomass. The accumulation process was only minimally affected by temperature variations between 5 and 40Â°C or high ambient concentrations of sodium chloride. The accumulation process was however considerably affected by variations in pH, bioaccumulation being most efficient at pH 5 - 9 but becoming rapidly less so at either extreme of pH. Selection for copper resistant or tolerant yeast diminished the yeast's capacity for CuÂ²â º accumulation. For this and other reasons the development of heavy metal tolerance in yeasts was deemed to be generally counterproductive to heavy metal bioaccumulation. The yeast biomass was also capable of accumulating other heavy metal cations such as c0Â²â º or CdÂ²â º. The yeast biomass could be harvested after bioaccumulation by tangential filtration methods, or alternatively could be packed into hollow fibre microfilter membrane cartridges and used as a fixed-bed bioaccumulator. By immobilizing the yeast in polyacrylamide gel and packing this material into columns, cuÂ²â º, C0Â²â º or CdÂ²â º could be removed from influent aqueous solutions yielding effluents with no detectable heavy metal, until breakthrough point was reached. This capacity was hypothesized to be a function of numerous "theoretical plates of equilibrium" within the column. The immobilized biomass could be eluted with EDTA and recycled for further bioaccumulation processes with minor loss of bioaccumulation capacity. Yeast cells were fractionated to permit identification of the major cell fractions and molecular components responsible for metal binding. Isolation of the yeast cell walls permitted investigation of their role in heavy metal accumulation. Although the amino groups of chitosan and proteins, the carboxyl groups of proteins, and the phosphate groups of phosphomannans were found to be efficient groups for the accumulation of copper, the less effective hydroxyl groups of the carbohydrate polymers (glucans and mannans) had a similar overall capacity for copper accumulation owing to their predominance in the yeast cell wall. The outer (protein-mannan) layer of the yeast cell wall was found to be a better CuÂ²â º chelator than the inner (chitinglucan) layer. It appeared that the physical condition of the cell wall may be more important than the individual macromolecular components of the cell wall in metal accumulation. It was apparent that the cell wall was the major, if not the sole contributor to heavy metal accumulation at low ambient heavy metal concentrations. At higher ambient metal concentrations the cytosol and vacuole become involved in bioaccumulation. Copper and other metals caused rapid loss of 70% of the intracellular potassium, implying permeation of the plasma membrane. This was followed by a slower "leakage" of magnesium from the vacuole which paralleled CuÂ²â º accumulation, suggesting that it may represent some form of ion-exchange. An intracellular copper chelating agent of approximately 2 kDalton molecular mass was isolated from copper tolerant yeast. This chelator was not a metallothionein and bound relatively low molar equivalents of copper compared to those reported for metallothionein. Treatment of the biomass with hot alkali yielded two biosorbents, one soluble (which could be used as a heavy metal flocculent), and an insoluble biosorbent which could be formed into a granular product to be used in fixed-bed biosorption columns. The granular biosorbent could accumulate a wide range of heavy metal cations in a semispecific manner and could be stored in a dehydrated form indefinitely, and rehydrated when required. Bioaccumulation by live algae was investigated as an alternative to yeast based processes. Various strains of algae, of which Scenedesmus and Selenastrum were the most effective, were found to be capable of accumulating heavy metals such as CuÂ²â º, PbÂ²â º and CrÂ³â º.
Keywords: Yeast; Yeast fungi -- Biotechnology; Cations; Metal ions